iPSC modeling of RBM20-deficient DCM identifies upregulation of RBM20 as a therapeutic strategy - Briganti, Francesca; Sun, Han; Wu, Wei; Wu, Jingyan; Zhu, Chenchen; Liss, Martin; Karakikes, Ioannis; Rego, Shannon; Cipriano, Andrea; Snyder, Michael; Meder, Benjamin; Xu, Zhenyu; et al. (Cell reports, 2020)
Recent advances in induced pluripotent stem cell (iPSC) technology and directed differentiation of iPSCs into cardiomyocytes (iPSC-CMs) make it possible to model genetic heart disease in vitro. We apply CRISPR/Cas9 genome editing technology to introduce three RBM20 mutations in iPSCs and differentiate them into iPSC-CMs to establish an in vitro model of RBM20 mutant dilated cardiomyopathy (DCM). In iPSC-CMs harboring a known causal RBM20 variant, the splicing of RBM20 target genes, calcium handling, and contractility are impaired consistent with the disease manifestation in patients. A variant (Pro633Leu) identified by exome sequencing of patient genomes displays the same disease phenotypes, thus establishing this variant as disease causing. We find that all-trans retinoic acid upregulates RBM20 expression and reverts the splicing, calcium handling, and contractility defects in iPSC-CMs with different causal RBM20 mutations. These results suggest that pharmacological upregulation of RBM20 expression is a promising therapeutic strategy for DCM patients with a heterozygous mutation in RBM20.
Gesehen am 09.02.2021